Direct cell–cell contact between mature osteoblasts and osteoclasts dynamically controls their functions in vivo - Furuya, Masayuki; Kikuta, Junichi; Fujimori, Sayumi; Seno, Shigeto; Maeda, Hiroki; Shirazaki, Mai; Uenaka, Maki; Mizuno, Hiroki; Iwamoto, Yoriko; Morimoto, Akito; Hashimoto, Kunihiko; Ito, Takeshi; et al. (Nature communications, 2018)
Bone homeostasis is regulated by communication between bone-forming mature osteoblasts (mOBs) and bone-resorptive mature osteoclasts (mOCs). However, the spatial–temporal relationship and mode of interaction in vivo remain elusive. Here we show, by using an intravital imaging technique, that mOB and mOC functions are regulated via direct cell–cell contact between these cell types. The mOBs and mOCs mainly occupy discrete territories in the steady state, although direct cell–cell contact is detected in spatiotemporally limited areas. In addition, a pH-sensing fluorescence probe reveals that mOCs secrete protons for bone resorption when they are not in contact with mOBs, whereas mOCs contacting mOBs are non-resorptive, suggesting that mOBs can inhibit bone resorption by direct contact. Intermittent administration of parathyroid hormone causes bone anabolic effects, which lead to a mixed distribution of mOBs and mOCs, and increase cell–cell contact. This study reveals spatiotemporal intercellular interactions between mOBs and mOCs affecting bone homeostasis in vivo. Communication between osteoblasts and osteoclasts is essential for bone homeostasis, but the mode of interaction is unclear. The authors use intravital two-photon microscopy in mice to show that these cells directly interact, regulating activity of osteoclasts, and that the interaction is modulated by parathyroid hormone administration.